Associations of polypharmacy with clinical parameters, function, and health-related quality of life in psoriatic arthritis - DURUÖZ, MEHMET TUNCAY (My University, 2023)
ObjectiveThe aim of this study was to assess predictors of polypharmacy and its effect on health-related quality of life in patients with psoriatic arthritis (PsA).MethodsThis cross-sectional study was performed between February and December 2019. The number of medications was grouped into minor (2-4) and major (>= 5) polypharmacy. Functional status and quality of life were assessed using the Health Assessment Questionnaire and Short-Form 36, respectively. Clinical and demographic characteristics, physical function, and quality of life of the polypharmacy group were compared. Predictive factors for major polypharmacy were evaluated using a logistic regression analysis.ResultsThe mean age of the 100 patients (70 females and 30 males) with PsA was 48.43 +/- 12.94 years. The proportion of patients with major polypharmacy was 19%. The physical function subscale of Short-Form 36 was lower in the major polypharmacy group (p = 0.009). Univariable analysis revealed that sex, body mass index, disease duration, disease activity, psoriasis severity, dactylitis, enthesitis, PsA subtypes, smoking, and Health Assessment Questionnaire were not associated with major polypharmacy (p > 0.10). In the multivariable model, the number of comorbidities (odds ratio, 3.151; 95% confidence interval, 1.828-5.429; p = 60 years (odds ratio, 4.864; 95% confidence interval, 1.159-20.418; p = 0.031) were significantly associated with major polypharmacy.ConclusionsThe number of comorbid diseases and age >= 60 years were the factors associated with major polypharmacy in patients with PsA. Although physical function was not associated with polypharmacy, patients with major polypharmacy had poorer quality of life.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; psoriatic arthritis; polypharmacy; comorbidity; quality of life; physical function; RECOMMENDATIONS; PEOPLE; psoriatic arthritis; polypharmacy; comorbidity; quality of life; physical function